2011
DOI: 10.3892/etm.2011.205
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of serum vitamin D deficiency and insufficiency in cancer: Review of the epidemiological literature

Abstract: Abstract. Vitamin D deficiency has been found to be associated with a variety of cancers, including prostate, multiple myeloma, colorectal and breast cancer. Several studies have shown vitamin D levels to have an inverse relation with cancer mortality, while others have considered it a potential risk factor. Vitamin D is believed to influence cancer prevalence, risk and survival; hence the need to assess vitamin D levels in cancer. Although numerous studies have been conducted to demonstrate vitamin D deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 70 publications
1
30
0
2
Order By: Relevance
“…In 2014, a meta-analysis by Chowdhury et al [39] observed a 16% increase in mortality for every decline of 10 ng/mL in the serum vitD levels. Moreover, among cancer patients, a high prevalence (about 70%) of vitD deficiency has been reported [40] , lower in outpatients (48%) than inpatients (up to 97.5%) [41][42] . Accordingly, in our study, 68% of NEN patients had vitD deficiency, but in contrast to the studies that demonstrated an inverse correlation between vitD levels and colorectal carcinoma staging [43][44] , in this study no significant correlation with vitD levels and the staging or grading of the disease was found.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, a meta-analysis by Chowdhury et al [39] observed a 16% increase in mortality for every decline of 10 ng/mL in the serum vitD levels. Moreover, among cancer patients, a high prevalence (about 70%) of vitD deficiency has been reported [40] , lower in outpatients (48%) than inpatients (up to 97.5%) [41][42] . Accordingly, in our study, 68% of NEN patients had vitD deficiency, but in contrast to the studies that demonstrated an inverse correlation between vitD levels and colorectal carcinoma staging [43][44] , in this study no significant correlation with vitD levels and the staging or grading of the disease was found.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D exerts a protective role in colorectal cancer as shown by epidemiological studies, which link low vitamin D diet or circulating level of calcidiol (25-hydroxyvitamin D 3 ) with increased risk of colorectal cancer [141,142]. Mechanistic studies have shown that vitamin D (1,25(OH) 2 D 3 ) can antagonize Wnt signaling in human colon cancer cells in multiple ways [143] and influences inflammatory pathways involved in cancer progression such as COX-2 and NF-κB [144].…”
Section: Bioactive Dietary Components and Mirnamentioning
confidence: 99%
“…Receptors of vitamin D exist in various organs, including the breast. Relation of breast cancer risk and vitamin D status has been defined in many studies, but the true association is still not understood and needs further research (Chlebowski, 2011;Gupta et al, 2011;Jacobs et al, 2011;Yao et al, 2011;Lopes et al, 2012;Shao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Conversion to the main serum metabolite, 25-hydroxyvitamin D (25(OH)D), is completed mainly in the liver, which is then further hydroxalated in the kidney to produce 1,25dihydroxyvitamin D. The best measurement for assessing vitamin D status is plasma level of 25(OH)D (Eliassen et al, 2011;Gupta et al, 2011;Women's Hospital for breast cancer screening or any breast complaint, clinical breast examination was done for all women. Mammography was carried out for women above 40 years of age; ultrasonography was undertaken as indicated by the radiologist in this age group, and in all patients less than 40 years of age.…”
Section: Introductionmentioning
confidence: 99%